Illocutionary Speech Act of Indonesian Minister of Education about Education Policy on Kemendikbud RI Youtube Video - T Tressyalina; Ena Noveria; Ermawati Arief; Roza Muchtar; Aprilia Ariesti Miona (Pascasarjana ISBI Bandung Conference Series, 2025)
Adjustments to education policies must be conveyed clearly to the public. It is important for the Indonesian Minister of Education Indonesian Nadiem Makarim to choose the right speech act so that the speech conveyed is not only captured in the form of sentences but also has an effect in the form of community action after the educational policy. Therefore, the aim of this research is to identify and describe the types of speech acts used by Nadiem Makarim in conveying educational policies on Kemendikbud RI youtube account. This research is a qualitative descriptive. The data in the research are Nadiem Makarim's statements in conveying policy adjustments during the Covid-19 pandemic. The data source in the research was taken video from the Kemendikbud RI youtube account. The research results show that there are 3 types of speech acts used by Nadiem Makarim, including representative, directive speech act and declarative. Keywords: Illocution; Speech Act; pragmatics